UPAYA MENURUNKAN ANGKA DEMAM BERDARAH DENGUE (DBD) MELALUI PENGUATAN PERAN SISWA DI SDN 38 KURANJI KOTA PADANG - Syafrawati Syafrawati; Silvia Argameli; Fitia Oktari; Heru Satria Nanda Putra (LPPM Universitas Andalas, 2019)
The number of Dengue Hemorrhagic Fever sufferers in Indonesia has been fluctuated year by year. Kuranji district is an area that has the highest Dengue Hemorrhagic Fever cases in the city of Padang during 2015 and 2016. There were 168 cases in 2015 and increased to 201 cases in 2016. This community service aimed to reduce the Dengue Hemorrhagic Fever disease by strengthening the role of elementary school students. The target community service was elementary school students No. 38 in Kuranji district of Padang. The information was Introduced by health promotion using a media. Firstly, the executor introduced themselves to the participant of community service. Furthermore, pre test was conducted in order to know the knowledge of participants regarding the impact of Dengue Hemorrhagic Fever disease prior to the delivery of information. Delivery of information to students was done throught health promotion using a media. The material given was abaout the impact of Dengue Hemorrhagic Fever in in children and environment, consisted of understanding causes of Dengue Hemorrhagic Fever and efforfs to prevent the impact of Dengue Hemorrhagic Fever disease. Finally, the post test was conducted to participants in order to know the knowledge about the Dengue Hemorrhagic Fever after the information was given. At the end of this program, the executor asked some question to participants and for those who were able to answer correctly would have a reward.